Hot topics on fecal microbiota transplantation for the treatment of inflammatory bowel disease - Zhang, Xiaochen; Ishikawa, Dai; Ohkusa, Toshifumi; Fukuda, Shinji; Nagahara, Akihito (Frontiers in Medicine, 2022)
Inflammatory bowel disease (IBD) is a chronic intestinal mucosal inflammatory disease with complex etiology. Traditional anti-inflammatory treatment regimens have yielded unsatisfactory results. As research continues to deepen, it has been found that the gut microbiota of patients with IBD is generally altered. The presence of microorganisms in the human gastrointestinal tract is inextricably linked to the regulation of health and disease. Disruption of the microbiotic balance of microbiota in the gastrointestinal tract is called dysbiosis, which leads to disease. Therefore, in recent years, the exploration of therapeutic methods to restore the homeostasis of the gut microbiota has attracted attention. Moreover, the use of the well-established fecal microbiota transplantation (FMT) regimen for the treatment of Clostridioides difficile infection has attracted the interest of IBD researchers. Therefore, there are an increasing number of clinical studies regarding FMT for IBD treatment. However, a series of questions regarding FMT in the treatment of IBD warrants further investigation and discussion. By reviewing published studies, this review explored hot topics such as the efficacy, safety, and administration protocol flow of FMT in the treatment of IBD. Different administration protocols have generally shown reassuring results with significant efficacy and safety. However, the FMT treatment regimen needs to be further optimized. We believe that in the future, individual customized or standard FMT implementation will further enhance the relevance of FMT in the treatment of IBD.